TRY AND ERROR OPTIMIZATION OF SERVOHYDROLIC CONTROL SYSTEM FOR A PRESS MACHINE - Nasril, Nasril; Hendra, Hendra; Siagian, Indra S (UNIB Press, 2019)
Servo hydraulic control valve system of Aerotech A3200 was setted for press machine made by BPPT-MEPPO by such method a high accuration can be achieved for the geometry of workpiece. Parameters being tested were the input unit (step), time (ramp) and frequency (bode) to predict occuring circumstances and compared with experimental results. KPos affected on steady-state error value, time-setting and Fc. Ki affected on the steady-state error without changing the value of Fc and PM and errors transition, where in the value of the steady state error was inverted to the error transition. KP eliminated the steady-state errors. The optimized setting was achieved at Kpos = 28.5, Kp = 2.000.000, and Ki = 1970 with error transition state 66 µm and 3 µm steady. In PM = 89 deg with Fc = 177 hertz.